Potential product Development at Indonesian Islamic Banks Based on Sharia Economic - Mohammad Yusuf; Annisa Sanny; Zuhri Ramadhan (Proceeding of The International Conference on Business and Economics, 2023)
The government has high hopes for the benefits of Bank Syariah Indonesia because it is a momentum that will affect public awareness of the Islamic financial industry, especially Islamic banking. However, behind the opportunities of an industry there are challenges that must be resolved, as for these challenges are related to increasing financial literacy, how to adapt a new work culture which of course among the three previous Islamic banks has different characteristics, bank management that ensures that integration goes well without sacrificing previous quality resources, and how to create financial services that can compete and be able to accommodate and facilitate financing related to the main program of Islamic banks. The main potential for product development of Bank Syariah Indonesia can make the Islamic finance industry compete both regionally and internationally so that it can help the development of the national economy.